Migraine: Current Therapeutic Targets and Future Avenues - Arulmozhi, D. K.; Veeranjaneyulu, A.; Bodhankar, S. L. (Current Vascular Pharmacology, 2006)
Migraine is characterized by attacks of intense pulsatile and throbbing headache, typically unilateral in nature with or without aura. Migraine affects a substantial fraction (10-20 %) of the world population (more women than men). With regard to the pathophysiology of migraine, several theories have been proposed; the major three are vascular (due to cerebral vasodilatation), neurological (abnormal neurological firing) and neurogenic dural inflammation (release of inflammatory neuropeptides). The drugs used to treat migraine can be divided into two groups: agents that abolish the acute migraine headache and agents aimed at prevention. The acutely acting antimigraine agents (5-HT1B/1D receptor agonists) stimulated research interest in the field of migraine. Currently prophylactic treatments for migraine include calcium channel blockers, 5-HT2 receptor antagonists, beta-adrenoceptor blockers and γ-amino butyric acid (GABA) agonists. Unfortunately, many of these treatments are non-specific and not always effective. Despite progress, the complex etiology of migraine requires further research, the condition often remains undiagnosed and available therapies are underused. In this review, the evidence that linked the different theories of migraine with its pathophysiology is considered. Furthermore, the present therapeutic targets and future approaches for the acute and prophylactic treatment of migraine are critically evaluated.
Keywords: headache